Opportunities for Practicing Sustainable Building Construction in Kurdistan Region, Iraq - Lawand Wirya Shawkat; Salar Salah Muhy Al-Din; Dusko Kuzovic (Journal of Contemporary Urban Affairs, 2018)
The construction sector of the Kurdistan region of the Republic of Iraq has witnessed a huge development in the construction sector last ten years. However, there is a lack of awareness and legislation regarding sustainable construction in the buildings sector. The aim of the paper is to find the required mechanism to introduce sustainable practice and implement sustainable construction in the buildings construction sector in Northern Iraq. The main objectives of this study are identifying the barriers in sustainable construction in Northern Iraq and investigate the law and regulations in dealing with these barriers.